Optimizing the Initial Current Control of a Single-Phase Induction Motor Using the Arduino Nano Soft Start Module - Nisa', Silvi Nur Rakhman; Ibrohim; Rijanto, Tri; Haryudo, Subuh Isnur (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2026)
Single-phase induction motors are widely used in domestic and industrial applications, but they have the main disadvantage of significant initial current surges, which have the potential to damage components and degrade power quality. This research proposes a solution through the design and implementation of an Arduino Nano-based soft start automation system to overcome these surges. The developed system uses Arduino Nano as the main microcontroller integrated with the PZEM-004T sensor for real-time monitoring of electrical parameters, as well as relays as an efficient switching mechanism. The method applied is the manipulation of the value of the resistor to limit the initial current, with the aim of measuring the effectiveness of the system in reducing the current surge. Focusing on testing a fully functioning system, the study is expected to prove a drastic decrease in initial current spikes. The results of this study can show that the Arduino Nano-based soft start automation system is effective in improving the performance and efficiency of induction motors, as well as being a practical guide for similar applications in the industry.